Quality of life with talazoparib after platinum or multiple cytotoxic non-platinum regimens in patients with advanced breast cancer and germline BRCA1/2 mutations: patient-reported outcomes from the ABRAZO phase 2 trial - Hurvitz, S. A.; Quek, R. G. W.; Turner, N. C.; Telli, M. L.; Rugo, H. S.; Mailliez, A.; Ettl, J.; Grischke, E.; Mina, L. A.; Balmana, Judith; Fasching, Peter; Bhattacharyya, H.; et al. (European Journal of Cancer, 2018)
BACKGROUND: Talazoparib (1 mg/day) exhibited promising efficacy and safety in patients with advanced breast cancer during ABRAZO (NCT02034916); this study evaluated patient-reported outcomes (PROs). PATIENTS AND METHODS: ABRAZO is a two-cohort, two-stage, phase 2 study of talazoparib in patients with advanced breast cancer after a response to prior platinum-based therapy (cohort 1 [C1], n = 49) or ≥3 platinum-free cytotoxic-based regimens (cohort 2 [C2], n = 35). PROs were assessed on day 1 (baseline), every 6 weeks for an initial 24 weeks, and every 12 weeks thereafter until progression, using the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (QLQ-C30) and its breast cancer module, QLQ-BR23. RESULTS: Global health status/quality of life (GHS/QoL) was maintained from baseline across all time points for both C1 and C2. For C1 and C2, median time to deterioration (TTD) of GHS/QoL (95% confidence interval [CI]) was 2.8 (2.1, 3.0) and 5.5 (4.2, 5.7) months, respectively. Median TTD for all QLQ-C30 functional scales for C1 and C2 ranged 2.1-3.1 months and 4.2-5.6 months, respectively; median TTD for all QLQ-BR23 symptom scales ranged 2.6-4.0 months and 4.2-5.6 months, respectively. There were no statistically significant differences in estimated overall change from baseline in the GHS/QoL scale for both cohorts (C1: -2.6 [95% CI, -7.8, 2.5]; C2: 1.2 [95% CI, -5.5, 8.0]). Significant overall improvements in the breast symptoms and arm symptoms and the future perspective of patients in C1 and C2 were observed, despite the statistically significant and clinically meaningful overall deterioration among patients regarding their role functioning (in C1) and dyspnoea symptoms (in C2). CONCLUSION: Despite the statistically significant and clinically meaningful overall deterioration among patients regarding their role functioning (in C1) and dyspnoea symptoms (in C2), patients in both C1 and C2 reported significant overall improvements in their breast symptoms, arm symptoms and future perspective, and their GHS/QoL was maintained from baseline.
EVALuna2:202806